2020
DOI: 10.2147/ott.s260191
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNAHIF1A-AS2 Promotes Renal Carcinoma Cell Proliferation and Migration via miR-130a-5p/ERBB2 Pathway</p>

Abstract: Background Long non-coding RNAs (lncRNAs) are essential for tumorigenesis and progression of diverse cancers. This study aims to investigate the roles of lncRNAs on renal carcinoma. Methods The expression of lncRNA HIF1A-AS2 in clear cell renal cell carcinoma (ccRCC) and adjacent non-cancer tissues was identified by quantitative real-time PCR (qRT-PCR). Investigations were performed on biological function of lncRNA HIF1A-AS2 on cell proliferation, cell cycle, apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Moreover, miRNA-155 has been acknowledged in cancer drug resistance and as a target for miRNA-based therapy. Several reports have demonstrated that miRNA-130a-5p is aberrantly expressed in various cancers, including lung cancer [ 8 ], gastric carcinoma [ 9 ], and renal carcinoma [ 10 ]. Besides, miRNA-130a-5p can also regulate chemosensitivity, proliferation, and metastasis in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNA-155 has been acknowledged in cancer drug resistance and as a target for miRNA-based therapy. Several reports have demonstrated that miRNA-130a-5p is aberrantly expressed in various cancers, including lung cancer [ 8 ], gastric carcinoma [ 9 ], and renal carcinoma [ 10 ]. Besides, miRNA-130a-5p can also regulate chemosensitivity, proliferation, and metastasis in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also provided more and more evidenced proofs on the important functions of ncRNAs in renal disease or kidney cancers. For example, Shi demonstrated a high expression of lncRNA H19 in the diabetic kidney and in TGF-β2-induced fibrosis in HMVECs, and inhibition of H19 attenuated kidney fibrosis and restored the normal kidney structure (Shi et al, 2020); Zhu suggested that lncRNAHIF1A-AS2 promotes renal carcinoma cell proliferation and migration via the miR-130a-5p/ERBB2 pathway (Zhu et al, 2020); Ai verified that miR-130a-3p facilitates the TGF-β1/Smad pathway in renal tubular epithelial cells and may participate in renal fibrosis by targeting SnoN, which could be a possible strategy for renal fibrosis treatment (Ai et al, 2020). However, the precise mechanism by which LncRNA H19 and miR-130a regulate the AKI process remains unknown, and in vivo studies and clinical data revealing the role of LncRNA H19 and miR-130a in AKI pathogenesis are FIGURE 7 | Potential mechanism elucidating the relationship and interplay of the LncRNA H19/miR-130a/BCL2L11 regulation axis in the human renal proximal tubular cell (HK-2) cellular process under H/R conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2B-AS1 overexpression was positively correlated with poor overall survival in RCC patients, and miR-141 expression could also effectively distinguish malignant tissues from non-malignant tissues. Zhu et al [30] found that lncRNA HIF1A-AS2 was highly expressed in renal carcinoma tissues and renal clear cell carcinoma cells. In vivo, HIF1A-AS2 interferes with cell proliferation, invasion and migration, and accelerates cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%